How do you find the inverse of f(x)= 2x +3?

2 Answers
Mar 24, 2018

f^-1(x)=(x-3)/2

Explanation:

y=f(x)

y=2x+3

Switch the places of x and y:

x=2y+3

Solve for y:

2y=x-3

y=(x-3)/2

f^-1(x)=(x-3)/2

Mar 24, 2018

y=(x-3)/2

Explanation:

Now, the inverse of a function is just writing x in terms of y

So f(x)=2x+3 becomes y=2x+3

y=2x+3 becomes y-3=2x

y-3=2x becomes (y-3)/2=x

or x=(y-3)/2

Finally just interchange x and y because we want the function in terms of x.
y=(x-3)/2

So f^-1(x)=(x-3)/2